Carborane Substituents Promote Direct Electrophilic Insertion over Reduction–Metalation Reactions. Issue 14 (2nd March 2016) - Man, Wing Y.; Ellis, David; Rosair, Georgina M.; Welch, Alan J.
Abstract: Two‐electron reduction of 1, 1′‐bis( o ‐carborane) followed by reaction with [Ru(η‐mes)Cl2 ]2 affords [8‐(1′‐1′, 2′‐closo‐C2 B10 H11 )‐4‐(η‐mes)‐4, 1, 8‐ closo ‐RuC2 B10 H11 ]. Subsequent two‐electron reduction of this species and treatment with [Ru(η‐arene)Cl2 ]2 results in the 14‐vertex/12‐vertex species [1‐(η‐mes)‐9‐(1′‐1′, 2′‐ closo ‐C2 B10 H11 )‐13‐(η‐arene)‐1, 13, 2, 9‐ closo ‐Ru2 C2 B10 H11 ] by direct electrophilic insertion, promoted by the carborane substituent in the 13‐vertex/12‐vertex precursor. When arene=mesitylene (mes), the diruthenium species is fluxional in solution at room temperature in a process that makes the metal–ligand fragments equivalent. A unique mechanism for this fluxionality is proposed and is shown to be fully consistent with the observed fluxionality or nonfluxionality of a series of previously reported 14‐vertex dicobaltacarboranes. Abstract : Take two : Two‐electron reduction of 1, 1′‐bis( o ‐carborane) and subsequent metalation with Ru(mes) 2+ results in a 4, 1, 8‐RuC2 B10 species. A further two‐electron reduction allows a direct electrophilic insertion reaction promoted by the carborane substituent for the addition of a second metal fragment and the formation of 1, 13, 2, 9‐Ru2 C2 B10 . A mechanism is proposed to rationalize the observed fluxionality of the products.